Psychometric properties of the Arabic emotional and behavioral reaction to intrusions questionnaire among sample of Arabic speaking adults - Emmanuelle Awad; Diana Malaeb; Amthal Alhuwailah; Mai Helmy; Muna Barakat; Rabih Hallit; Sami El Khatib; Mohamad Rahal; Syed Arman Rabbani; Reem Alzayer; Nada H. Farrag; Rita El Hajjar; et al. (Scientific Reports)
Abstract Background Intrusive “thoughts” represent undesirable cognitive activity that can cause distress, and occurs in individuals with and without psychological disorders. In order to deal with unwanted intrusive thoughts, individuals might consciously attempt to halt the flow of these cognitions through suppression or unconsciously avoid them automatically through repression. This study aimed to psychometrically evaluate and validate a translation of the Emotional and Behavioral Reaction to Intrusions Questionnaire (EBRIQ) in Arabic, for adults who speak the language. Methods The snowball sampling technique was used to recruit adults (n = 755) from five Arab countries (Lebanon, United Arab Emirates, Egypt, Jordan, and Kuwait), who completed the Arabic EBRIQ. A Confirmatory Factor Analysis (CFA) was conducted to examine the factor structure of the EBRIQ. Results A total of 755 participants completed the survey, with a mean age of 21.89 ± 4.18 years and 77.5% females. CFA indicated a modest fit for the one-factor model. Internal reliability was excellent (ω = 0.96; α = 0.96). No significant difference was found in terms of EBRIQ scores between males (M = 10.37, SD = 7.80) and females (M = 10.52, SD = 7.99) in the total sample, t(753) = − 0.22, p = .830. The highest EBRIQ scores were found in Jordanian participants (12.55 ± 6.94), followed by Emirati (12.23 ± 8.20), Lebanese (11.12 ± 7.69), Egyptian (8.96 ± 8.05) and Kuwaiti (8.20 ± 7.75) participants, F(4, 750) = 10.36, p < .001. Conclusion This study suggests that our Arabic translation of the EBRIQ is psychometrically proven to be reliable for use in Lebanon, United Arab Emirates, Egypt, Jordan, and Kuwait. This validated tool will allow researchers and practitioners to assess emotions and behaviors related to intrusive thoughts.